Daniel Read Larned papers - Larned, Daniel Read.
Chiefly letters written by Larned to his sisters and brother-in-law pertaining primarily to General Ambrose Everett Burnside's expedition to North Carolina. Includes descriptions of the battles of Beaufort, Fort Macon, New Bern, and Roanoke Island, N.C. Other subjects include the battles of Antietam, Md., and Cold Harbor, Fredericksburg, Spotsylvania, and Wilderness, Va.; and the sieges of Petersburg, Va., and Knoxville, Tenn. Larned describes the pursuit of Confederate general John Hunt Morgan in Ohio and Burnside's interactions with Generals H.W. Halleck, George Brinton McClellan, and William S. Rosecrans. Other subjects include military organization, disputes over rank, discipline, morale, African American troops, entertainment, prisoners of war, foraging expeditions, inflation, disease, furloughs, and the effect of the war on noncombatants in the South. Includes a book inscribed by Burnside to Larned and photographs of Larned.
Typewritten transcripts are available for part of the collection.
Army officer and private secretary to Gen. Ambrose Everett Burnside during the Civil War. Born 1828.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Burnside, Ambrose Everett, -- 1824-1881.; Halleck, H. W. -- 1815-1872.; McClellan, George Brinton, -- 1826-1885.; Morgan, John Hunt, -- 1825-1864.; Rosecrans, William S. -- 1819-1898.; Leonard family -- Correspondence; Larned family -- Correspondence; United States. -- Army -- History -- Civil War, 1861-1865.; Antietam, Battle of, Md., 1862.; Cold Harbor, Battle of, Va., 1864.; Fredericksburg, Battle of, Fredericksburg, Va., 1862.; New Bern, Battle of, New Bern, N.C., 1862.; Spotsylvania Court House, Battle of, Va., 1864; Wilderness, Battle of the, Va., 1864.; Beaufort (N.C.) -- Siege, 1862.; Confederate States of America -- History; Fort Macon (N.C.) -- Siege, 1862.; Knoxville (Tenn.) -- Siege, 1862.; North Carolina -- History -- Civil War, 1861-1865.; Maryland -- History -- Civil War, 1861-1865.; Ohio -- History -- Civil War, 1861-1865.; Petersburg (Va.) -- History -- Siege, 1864-1865.; Roanoke Island (N.C.) -- History -- Capture, 1862.; Tennessee -- History -- Civil War, 1861-1865.; Virginia -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Economic aspects; United States -- History -- Civil War, 1861-1865 -- Medical care; United States -- History -- Civil War, 1861-1865 -- Participation, African American; United States -- History -- Civil War, 1861-1865 -- Prisoners and prisons; United States -- History -- Civil War, 1861-1865 -- Psychological aspects; Army officers